Research handbook on the sociology of international law - Hirsch, Moshe; Lang, Andrew (Cheltenham, UK ; Northampton, MA : Edward Elgar Publishing, 2018)
This innovative Research Handbook explores recent developments at the intersection of international law, sociology and social theory. In doing so, it highlights anew the potential contribution of sociological methods and theories to the study of international law, and illustrates their use in the examination of contemporary problems of practical interest to international lawyers. The diverse body of expert contributors discuss a wide range of methodologies and approaches – including those inspired by the giants of twentieth century social thought, as well as emergent strands such as computational linguistics, performance theory and economic sociology. With chapters exploring topical areas including the globalization of law, economic globalization, property rights, global governance, international legal counsel, social networks, and anthropology, the Research Handbook presents a number of paths for future research in international legal scholarship. Full of original insight, this interdisciplinary Research Handbook will be essential reading for academics and scholars in international law and sociology, as well as postgraduate students. Lawyers practicing in international law will also find this a stimulating read.
Introduction / Moshe Hirsch, Andrew Lang -- Issues of empire, contestation, and hierarchy in the globalization of law / Bryant G. Garth -- A conflicts-law response to the precarious legitimacy of transnational trade governance / Fabian Bohnenberger, Christian Joerges -- Correlated ownership : Polanyi, Commons, and the property continuum / Sabine Frerichs, Rick James -- Regulating speed : social acceleration and international law / Wouter G. Werner -- 'What gets measured gets done' : exploring the social construction of globalized knowledge for development / Ruth Buchanan, Kimberley Byers, and Kristina Mansveld -- International lawyers and the study of expertise : representationalism and performativity / Andrew Lang -- Ignorance/power : rule of law reform and the administrative law of global governance / Deval Desai -- Reflexive sociology of international law : Pierre Bourdieu and the globalization of law / Mikael Rask Madsen -- The practice of litigation at the ICJ : the role of counsel in the development of international law / Gregory Messenger -- International investment law as formally rational law : a Weberian analysis / David Schneiderman -- Practice theory and international law / Jeffrey L. Dunoff and Mark A. Pollack -- The 'practice turn' in international law : insights from the theory of structuration / Nicolas Lamp -- An anthropological approach to international economic law / Galit A. Sarfaty -- Network analysis and the sociology of international law / Sergio Puig -- Social networks and the enforcement of international law / Shai Dothan -- Locked in language : historical sociology and the path dependency of investment treaty design / Wolfgang Alschner -- Social constructivism and the social construction of world economic reality / Sungjoon Cho -- Core sociological theories and international law / Moshe Hirsch.
Sisältää bibliografisia viitteitä ja hakemiston.
Keywords: International law; Sociological jurisprudence; kansainvälinen oikeus; oikeussosiologia; yhteiskuntateoriat; globaali hallinta; globalisaatio; internationell rätt; rättssociologi; samhällsteorier; global styrning; globalisering